To Vote is to Dine with the Devil: Using Host Communities and Higher-institutions’ Relationship between 1999 and 2015 General Elections in Osun State, Nigeria (Journal of Management and Social Sciences, 2017)
AbstractA steady decline in voter turnout has been noticed in general elections in Nigeria. Past studies have focused on rural dwellers' voting behaviour but there is still a dearth of research on the voting behaviour of host communities of higher institutions. This paper therefore examines the turnout of residents in host communities of higher institutions between 1999 and 2015 general elections in Osun state, Nigeria. Social disorganization theory provides the analytical framework for the study. Twelve host communities and twelve neighbouring communities were selected from twelve higher institutions. Questionnaires were administered to 2,520 respondents; 63 respondents were interviewed and records were sought. Majority of the respondents were very passive voters. There was a significant association between the respondents' turnout (χ²=19.3) and students' relationship, disturbance from student cultists and thugs (χ²=22.1) and their voters' turnout. Constant attack by aggressive students prior to elections created fear in residents. The paper concludes that students' negative behaviour affects residents' turnout. There is a need to educate students to shun cultism and thuggery and to obey constituted authority of the host communities. KeywordsVote, dine with the Devil, higher-institution and host-community relationship, 1999